Performance evaluation of improved practical control method for two-mass PTP positioning system - Mohd. Yakub, Mohd. Fitri; Martono, Wahyudi; Akmeliawati, Rini (2010)
This paper introduces improvement in a practical nominal characteristic trajectory following (NCTF) controller for two mass point-to-point (PTP) rotary positioning systems. The NCTF controller consists of a nominal characteristic trajectory (NCT) as a movement reference and a compensator. The objective of the NCTF controller is to make the object motion follow the NCT and end at its origin. The NCTF controller is designed based on a simple open-loop experiment of the object and an exact model and known parameters is not necessary for controller design. New improvement practical method has been developing by adding a notch filter as a compensator to eliminate the vibration that caused by mechanical resonance. The improved NCTF controller is evaluated and discussed through experimental. The effect of the design parameters on the robustness of the improved NCTF controller to inertia is evaluated and compared with conventional PID controller. It is shown that improved NCTF controller has a consistent performance in comparison with the conventional PID controller